New Attorney Swearing In Ceremony Held in State Building Auditorium - Watkins, Howard::::::::: (1987)
New admittees smiling as they take their attorney oath 1st row: Patricia Mattson-Markell and James Sanchez; 2nd: Cathy Basham, and Fred Silva